(untitled) (Bangladesh Journal of Botany, 2019)
Experiments were conducted to study the deleterious impacts of low intensity light on physiochemical and agronomic attributes of tobacco, to evaluate varying doses of foliar 5-aminolevulinic acid (5-ALA) for alleviation of adverse impacts of low light intensity and to observe either 5-ALA modulated physiochemical regulations impart stress tolerance at agronomic level. Significant decrease of biomass accumulation, synthesis of osmo-protectants, chlorophyll contents, and chlorophyll fluorescence and increase in malondialdehyde were recorded compared to control. Exogenous application of 5-ALA excellently alleviated adverse impacts of low light intensity stress on agronomic and physiochemical attributes of tobacco seedlings. Conclusively, Light stress had adverse implications on all studied attributes while 5-ALA at 10-20 mg/l had remarkable alleviated deleterious impacts of light stress on plant.